Simultaneous determination of α-amyrin and β-sitosterol in Centranthus longiflorus Stev. Subsp. longiflorus Stev and Iris taochia Woronow ex Grossh by GC-MS method - Askin, Hakan; Yilmaz, Bilal; Bakirci, Seyma; Ayar, Arif (Progress in Nutrition, 2018)
Turkey is rich in terms of triterpenes and sterols flora. Triterpenes and sterols hold out for medicinal advances and new drugs. This paper describes a simple, precise, sensitive and specific method for the simultaneous determination of α-amyrin and β-sitosterol in Centranthus longiflorus and Iris taochia by gas chromatography-mass spectrometry (GC-MS) method. The retention times of α-amyrin and β-sitosterol were found 16.1 and 15.1 min, respectively. The linear ranges in this developed method were 1-100 and 5-750 µg/mL for α-amyrin and β-sitosterol, respectively. The intra- and inter-day precisions, expressed as the relative standard deviation (RSD), were less than 4.97 and 4.99%, determined from quality control samples for α-amyrin and β-sitosterol, and accuracy was within 2.00 and 4.60% in terms of relative error, respectively. The percentage recovery obtained for α-amyrin and β-sitosterol were 99.7 and 99.8%, respectively. Limit of detection and quantification for α-amyrin were 5 and 15 ng/mL, for β-sitosterol 50 and 150 ng/mL, respectively. The developed method can be used for routine quality control analysis of α-amyrin and β-sitosterol in dried whole plant of Centranthus longiflorus and Iris taochia.